Miniplate-Aided Mandibular Dentition Distalization as a Camouflage Treatment of a Class III Malocclusion in an Adult - Zaki Hakami; Po Jung Chen; Ahmad Ahmida; Nandakumar Janakiraman; Flavio Uribe (Hindawi Limited, 2018)
This case report describes orthodontic camouflage treatment for a 32-year-old African American male patient with Class III malocclusion. The treatment included nonextraction, nonsurgical orthodontic camouflage by en masse distalization of the mandibular teeth using skeletal anchorage devices. The total treatment time was 23 months. Normal overjet and overbite with Class I occlusion were obtained despite the compensated dentition to the skeletal malocclusion. His smile esthetics was significantly improved at the completion of his treatment.